DETERMINAN PENINGKATAN BERAT BADAN PADA BALITA DI DESA BONCAH MAHANG KABUPATEN BENGKALIS - Dona Martilova; Lika Kusuma Wardani (IKES Payung Negeri Pekanbaru, 2025)
Nutritional problems in toddlers are still a public health challenge in Indonesia. Factors such as exclusive breastfeeding, maternal employment, and family income contribute to the nutritional status of toddlers. This study aims to analyze the determinants of weight gain in toddlers in Boncah Mahang Village. A type of quantitative research with a cross sectional design. The population is mothers with toddlers (ages 12-59 months), as many as 114 respondents. Data analysis used Chi square test and Logistic Regression. This research was carried out in Boncah Mahang Village, Bengkalis Regency. This research was conducted in May-June 2024. The method of collecting data through questionnaires, which was previously tested for validates and reliability on the questionnaire, the results of the study showed that there was an influence on education level, employment status, income, knowledge, and exclusive breastfeeding history significantly related to weight gain in toddlers (p < 0.05). The results of the multivariate analysis showed three dominant variables, namely employment status (Exp B = 7,695), income (Exp B = 3,560), and exclusive breastfeeding history (Exp B = 27,210). The predictive model produced showed that in the condition that mothers do not exclusively breastfeed, have low income, and do not work, toddlers have a 99.99% chance of not experiencing weight gain. Maternal employment status, family income, and exclusive breastfeeding history are the main determinants of weight gain in toddlers. The results of this predictive model can be the basis for nutrition intervention planning and public health policies, especially in improving the nutritional status of children in rural areas.